2010
DOI: 10.1007/s00244-010-9532-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Geochemical Mobility of Metals in Surface Sediments of the Santa Rosalia Mining Region, Western Gulf of California

Abstract: To asses the geomobility of cadmium, copper, iron, manganese, nickel, lead, and zinc in marine sediments near the Santa Rosalía copper smelter, which is located on the eastern coast of the Baja California Peninsula, sequential leaching was applied to sediment samples containing different levels of Cu: (1) uncontaminated or slightly contaminated (<55 mg kg⁻¹ Cu); (2) moderately contaminated (55-500 mg kg⁻¹ Cu); and (3) heavily contaminated (>500 mg kg⁻¹ Cu). Concentrations of Cd, Cu, Fe, Mn, Ni, Pb, and Zn in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
14
1
2
Order By: Relevance
“…These differences may be due to the natural composition of the sediments, and more importantly, they are related to industrial activities, such as mining and agriculture (Ghrefat et al 2012;Li et al 2011;Ochoa-Valenzuela et al 2009). Mn concentrations were similar to those (from 125.36 to 416.31 mg/kg) previously reported by Ochoa-Valenzuela et al (2009) in sediments located in Bacochibampo Bay, Sonora, Mexico, but lower than those values (from 50 to 32,600 mg/kg) reported by Shumilin et al (2011) in surface sediments of the Western Gulf of California.…”
Section: Chemical Composition and Total Fe And Mn Content In Surface supporting
confidence: 87%
See 2 more Smart Citations
“…These differences may be due to the natural composition of the sediments, and more importantly, they are related to industrial activities, such as mining and agriculture (Ghrefat et al 2012;Li et al 2011;Ochoa-Valenzuela et al 2009). Mn concentrations were similar to those (from 125.36 to 416.31 mg/kg) previously reported by Ochoa-Valenzuela et al (2009) in sediments located in Bacochibampo Bay, Sonora, Mexico, but lower than those values (from 50 to 32,600 mg/kg) reported by Shumilin et al (2011) in surface sediments of the Western Gulf of California.…”
Section: Chemical Composition and Total Fe And Mn Content In Surface supporting
confidence: 87%
“…The total Fe and Mn values were found to be slightly higher than those values (from 0.6 to 1.72 %) reported by Ochoa-Valenzuela et al (2009) in surface sediments from Bacochibampo Bay, located south of Sonora, Mexico, but lower than those levels (from 21,800 to 102,400 mg/kg) reported by Shumilin et al (2011) in surface sediments of the Western Gulf of California. These differences may be due to the natural composition of the sediments, and more importantly, they are related to industrial activities, such as mining and agriculture (Ghrefat et al 2012;Li et al 2011;Ochoa-Valenzuela et al 2009).…”
Section: Chemical Composition and Total Fe And Mn Content In Surface contrasting
confidence: 70%
See 1 more Smart Citation
“…This area displays high levels of metals that are associated with former copper mining and smelting activities that were performed for nearly a century (Wilson and Rocha, 1955;Rodríguez Figueroa, 2004). There is clear evidence of the pollution of surface sediments by such solid waste dumping (Shumilin et al, 2000;Rodríguez Figueroa, 2004, 2010; however, recent data were somewhat encouraging, as the heavy metals from highly polluted sites were shown to be mainly concentrated in the residual fraction of the surface sediments (Shumilin et al, 2011). Additionally, an analysis of the metal levels in brown seaweeds showed that most toxic metals were retained in the sediments and were not released to the water column (Choumiline et al, 2006;Rodríguez Figueroa, 2010;Rodríguez-Figueroa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque los sedimentos de los ríos Calera, Amarillo y Puyango muestran concentraciones de Mn, Cu, Co y Ni inferiores a las encontradas en sedimentos de zonas marino-costeras ubicadas en la Península de Baja California (México), también impactadas por la explotación minera del Cobre (Shumilin et al 2011, Shumilin et al 2013, las concentraciones de Pb y Zn en los sedimentos del Puyango son superiores a las de los sedimentos de esas zonas de México. Los resultados obtenidos en este estudio también indican que las concentraciones de Mn, Pb, Cu y Zn en los sedimentos del Puyango son mayores a las concentraciones de estos mismos elementos reportadas por Adánez et al (2014) en los sedimentos de los ríos Odiel y Tinto (Mn 717 y 187 mg/kg, Pb 212 y 977 mg/kg, Cu 1220 y 535 mg/kg y Zn 452 y 232 mg/kg), ríos que drenan cuencas localizadas en la Faja Pirítica Ibérica (Huelva, España) y que han sido fuertemente afectados por las actividades mineras y el drenaje ácido de minas por más de 5000 años (Cánovas et al 2007).…”
Section: Cuadro III Concentraciones Promedio De Los Elementos Determunclassified